#TITLE_ALTERNATIVE# - ILYAS (NIM 102 04 071), ADRINAL
Seismic rock physics is a connector between seismic data and the in situ condition of reservoir. It cans modeless the fluid on the rock and its effect to seismic wave properties. Fluids substitution is an important thing to be done in seismic rock physics studies. Fluid substitution represents a part of seismic modeling and qualification of various fluid substitutions scenarios which can not only give clue to AVO response but also to seismic post data for direct hydrocarbon indicator or DHI. Fluid substation involves Gassmann equation (approximation of low frequency). Problem in fluid substitutions predicting seismic velocity of rock are affect of fluid saturated, effect of pore of matrix. Gassmann equation will estimate fluid effect to bulk modulus properties. Prediction of bulk modulus properties can used to analyze DHI like spot bright amplitude and AVO.